Playing football on artificial turf as a risk factor for fifth metatarsal stress fracture: a retrospective cohort study. Issue 2 (20th February 2019) - Miyamori, Takayuki; Nagao, Masashi; Sawa, Ryuichi; Tumilty, Steve; Yoshimura, Masafumi; Saita, Yoshitomo; Ikeda, Hiroshi; Kaneko, Kazuo
Abstract : Objective: The fifth metatarsal stress fracture is a common injury among football players. Although several risk factors have been proposed, the association between the playing surface and development of fifth metatarsal stress fractures (MT-5) has not been evaluated. We conducted an epidemiological study using a computer-based survey to investigate the association between the playing surface and development of MT-5. Methods: This study included 1854 football players, of which 41 experienced MT-5 within the past 24 months. Baseline demographic data and the percentage of time spent playing on artificial turf and clay fields were compared between the non-MT-5 and MT-5 player groups, and the risks for development of MT-5 associated with the playing surfaces were estimated by univariate and multivariate analyses. Results: There were significant differences in body mass index, years of play, playing categories and playing time on artificial turf between non-MT-5 and MT-5 groups (p<0.05). Generalised estimating equations analyses adjusted for multiple confounders demonstrated that relative to the risk of playing <20% of the time on each surface, the OR (OR: 95% CI) for MT-5 for playing on artificial turf >80% of the time increased (3.44: 1.65 to 7.18), and for playing on a clay field 61%–80% of the time, the OR decreased (0.25: 0.11 to 0.59). Conclusions: A higher percentage of playing time on an artificial turf was a risk factor for developing MT-5 in football players. This finding could be beneficial for creating strategies to prevent MT-5.